Diagnosis of lung adenocarcinoma in situ and minimally invasive adenocarcinoma from intraoperative frozen sections: an analysis of 136 cases. Issue 12 (12th May 2016) - He, Ping; Yao, Guangyu; Guan, Yubao; Lin, Yunen; He, Jianxing
Abstract : Aims: To determine the diagnostic accuracy and contraindications for intraoperative diagnosis of lung adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) from frozen sections. Methods: A retrospective analysis of data from 136 patients pathologically diagnosed with early-stage (T1N0M0) AIS or MIA from paraffin-embedded sections. The rate of concordance between the diagnoses from intraoperative frozen sections and paraffin-embedded sections was determined, and the interpretive features that contributed to errors and deferrals in frozen-section diagnoses were identified. Results: Of the 136 patients, diagnoses from frozen sections and paraffin-embedded sections were concordant in 86 (63.24%) cases intraoperatively diagnosed with AIS or MIA, and 44 (32.35%) cases were intraoperatively diagnosed with adenocarcinoma as the range of infiltration could not be determined from the frozen sections. From the remaining six (4.41%) cases, the frozen section and paraffin-embedded section diagnoses were discordant. The reasons for frozen section errors and deferrals included larger tumour volume, tumour located close to the visceral pleura, interstitial inflammation or fibrosis, absence of prominent atypia and differential morphology in the deeper levels of the paraffin block. Conclusions: Diagnosis of AIS and MIA from intraoperative frozen sections is feasible. We provide several modifications that may improve the diagnostic accuracy of intraoperative frozen sections for early-stage lung adenocarcinoma.